Innovative design and experimental verification of cam shedding for high-speed looms - Haifei Qiu; Ming Chen; Feiyang Li; Yifan Zhang (Alexandria Engineering Journal)
For overcoming space limitations and load-bearing defects of traditional conjugate cam shedding on looms, a novel cam shedding system with double-shaft was developed by incorporating mechanism analysis, theoretical calculations, modeling and simulation, and experimental verification. The lifting motion of the heald frame is controlled by the cosine acceleration law, with MATLAB compiling the reverse program of the cam theoretical profile. A functional digital prototype is created in ADAMS/View using planar rod groups, gear transmission, and conjugate cam mechanism. The simulation results of considering yarn tension exhibited highly consistent swing arm and heald frame motion curves with numerical calculations, and the dynamic performance of the shedding system is affected by yarn tension, which leads to an increase in motor torque and acceleration oscillation in the low-frequency domain. Furthermore, an experimental proportional model was produced using 3D printing technology and tested for motion performance at varying rotational speeds, verifying the design's theoretical accuracy and practical feasibility, indicating that this mechanism runs smoothly and reliably in lifting and returning the heald frame by cam; meanwhile, the yarn deformation and shed characteristics are apparent, meeting the requirements of the shedding weaving process of plain fabric. The work in this paper effectively solves the problem of contact wear between the cam and rotor, which is conducive to design innovation and performance improvement of the conjugate cam shedding on high-speed looms.